Validity of sealant retention as surrogate for caries prevention--a systematic review. - Steffen Mickenautsch (Public Library of Science (PLoS), 2013)
Introduction/aim To appraise the clinical literature in determining whether loss of complete sealant retention as surrogate endpoint is directly associated with caries occurrence on sealed teeth as its clinical endpoint and to apply the appraised evidence in testing the null-hypothesis that the retention/caries ratio between different types of sealant materials (resin and glass-ionomer cement) is not statistically significant (= Prentice criterion for surrogate endpoint validity). Methods Databases searched PubMed/Medline, Directory of Open Access Journals; IndMed, Scielo. Systematic reviews were checked for suitable trials. The search terms: "fiss* AND seal*" and "fissure AND sealant" were used. Article selection criteria were: clinical trial reporting on the retention and caries occurrence of resin and/or glass-ionomer cement (GIC) fissure sealed permanent molar teeth; minimum 24-month follow-up period; systematic review or meta-analysis. Datasets and information were extracted from accepted trials. The principle outcome measure was the ratio of Risk of loss of complete retention to the Risk of caries occurrence per sealant type (RCR). Risk of bias was assessed in trials and sensitivity analysis with regard to potential confounding factors conducted. The null-hypothesis was tested by graphical and statistical methods. Results The risk of loss of complete retention of sealant materials was associated with the risk of caries occurrence for resin but not for GIC based sealants. The difference between RCR values of the two sealant types was statistically significant (p<0.05). The null-hypothesis was rejected. Conclusions The current clinical evidence suggests that complete retention of pit and fissure sealants may not be a valid surrogate endpoint for caries prevention as its clinical endpoint. Further research is required to corroborate the current results.